Going shopping - Garland, Sarah (London : Frances Lincoln Children's Books, 2008)
A mother, two children, and a dog take their car to the grocery store, shop, and return home with their purchases.
0.7
K-3
K-3
Keywords: Shopping -- Juvenile fiction; Shopping -- Fiction; Shopping -- Fiction